When the Personal Vote Is Not Enough: The Failure of Charter Reform in Columbia, South Carolina (Journal of Public and Nonprofit Affairs, 2018)
The choice of city structure is one of the most important choices that citizens and elected representatives face in local government. While we know a good deal about the macro-level trends in a city structure, we know comparatively less about why residents in individual cities may opt for one structure or another. In this paper, we focus on the unsuccessful 2013 single-issue referendum in Columbia, South Carolina, addressing why, despite support from key players, the city chose not to adopt a strong-mayor form of government. Using precinct-level data, we find support for the personal vote hypothesis. We discover that support for the sitting mayor is a significant predictor of support for reform, although the lack of voter mobilization city-wide may be too much of a factor for reform advocates to overcome. This investigation leads us to a number of conclusions that are relevant for both academics and practitioners who want to understand structural change in local government.